ANALISIS SISTEM PENCAHAYAAN DI RUANG SIPIL/SARANA DENGAN SNI NOMOR 03-6575-2001 TENTANG PERANCANGAN SISTEM PENCAHAYAAN BUATAN PT X GRESIK - Mualifah, Annida Khusnul; Denny, Hanifa Maher; Widjasena, Baju (Fakultas Kesehatan Masyarakat, 2015)
Intensityilluminationforoffice activityless than according to SNI 03-6575-2001 number 350 lux.Indoor lighting, especially in the workplace that does not meet certain requirements can worsen vision.Less of lighting will cause eyestrain which will then be lowered productivity.This study aimed to analyze the implementation of artificial lighting system and analyzes the factors that influence the artificial lighting system based SNI 03-6575-2001 numbers in the civil / PT X Gresik means.This research is a descriptive qualitative in-depth interviews.The subjects of this research were two people as the main informants and 2 as an informant triangulation.Supporting data used to use observation guidelines in the form.The results showed key informants in plan of lighting system using SNI energy conservation but based SNI 03-6575-2001 numbers do not meet the 66.7% standard rate.Factors that led to the implementation of less than standard lighting systems is the influence of power requirements, light requirements, armature or house lights are used, reflectance, average lighting level, color rendering, the window is not in accordance with the standard rate.Never been given training in planning lighting systems by PT X Gresik and evaluation and monitoring conducted K3, and Sipil, Enjinering.PT X need to provide training planning a lighting system to the main informant to improve the ability of planning a lighting system and making employment contracts K3 involvement in the planning, implementation, evaluation and monitoring.